DEAD-Box Protein-103 (DP103, Ddx20) Is Essential for Early Embryonic Development and Modulates Ovarian Morphology and Function - Mouillet, Jean-François (The Endocrine Society, 2008)
The DEAD-box helicase DP103 (Ddx20, Gemin3) is a multifunctional protein that interacts with Epstein-Barr virus nuclear proteins (EBNA2/EBNA3) and is a part of the spliceosomal small nuclear ribonucleoproteins complex. DP103 also aggregates with the micro-RNA machinery complex. We have previously shown that DP103 interacts with the nuclear receptor steroidogenic factor-1 (SF-1, NR5A1), a key regulator of reproductive development, and represses its transcriptional activity. To further explore the physiological function of DP103, we disrupted the corresponding gene in mice. Homozygous Dp103-null mice die early in embryonic development before a four-cell stage. Although heterozygous mice are healthy and fertile, analysis of steroidogenic tissues revealed minor abnormalities in mutant females, including larger ovaries, altered estrous cycle, and reduced basal secretion of ACTH. Our data point to diverse functions of murine DP103, with an obligatory role during early embryonic development and also in modulation of steroidogenesis.